2003
DOI: 10.1016/s0048-9697(02)00609-5
|View full text |Cite
|
Sign up to set email alerts
|

Trace element and nutrient accumulation in sunflower plants two years after the Aznalcóllar mine spill

Abstract: The failure of a tailing pond dam at the Aznalcóllar pyrite mine (SW Spain) in April 1998 released a toxic spill affecting approximately 4300 ha along the Agrio and Guadiamar valleys. Two years later, we have studied yield and concentration of mineral nutrients and trace elements in sunflower plants grown in the spill-affected soil, and in an adjacent unaffected soil as comparison. The study has been carried out in plants at seedling (V4) and mature (R8) stages. Shoot and root biomass of sunflower seedlings wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
85
1
3

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 166 publications
(95 citation statements)
references
References 32 publications
6
85
1
3
Order By: Relevance
“…In spite of the high doses of biosolids applied, extractable heavy metal concentrations were below the levels considered toxic to plants (Madejón et al, 2003). The high pH and the CaCO3 content of the soil justify the low levels of the DPTA-extractable heavy metals found.…”
Section: Discussionmentioning
confidence: 94%
“…In spite of the high doses of biosolids applied, extractable heavy metal concentrations were below the levels considered toxic to plants (Madejón et al, 2003). The high pH and the CaCO3 content of the soil justify the low levels of the DPTA-extractable heavy metals found.…”
Section: Discussionmentioning
confidence: 94%
“…Plants are known to take up and accumulate trace metals from contaminated soils (Singh and Narwal, 1984;Bojakowska and Kochany, 1985;Pulford and Watson, 2003;Madejon et al, 2003), hence detection in vegetable samples was not surprising. Although levels of 0.022 mg/kg and 0.015 mg/ kg of Cd and Pb in cabbage and 0.035 mg/kg and 0.018 mg/kg in spinach respectively are within the normal range in plant leaves (Table 6), continual consumption could lead to accumulation with adverse health implications since Cd has been linked to renal diseases and cancer (Kjellstroem, 1986).…”
Section: Resultsmentioning
confidence: 99%
“…Madejón et al [24] observed an As extraction of about 3 g·ha -1 by growing H. annuus in a soil polluted by a mine spill. In our case, sorghum removed about 220 g·ha -1 of As.…”
Section: Discussionmentioning
confidence: 99%